Symphysis menti: A strong indicator of osteoporosis - Dur-e-Shahwar Rehman; Naila Parveen; Imran Ishaq (Journal of Oral and Maxillofacial Radiology, 2016)
Context: Osteoporosis is a highly prevalent disease especially in elderly females. Orthopantomogram (OPG) X-ray is a commonly employed technique in dental clinics which shows bony details for both mandible and maxilla. It can be used as a window to the whole skeleton if the bone density changes on dual energy X-ray absorptiometry (DXA) scan correlates with the changes in the morphology of mandible. Aim: This study aims to establish a relation between changes in height of body of mandible at symphysis (HS) on OPG with DXA scan of the femoral neck and spine to see whether OPG can be employed for screening and early detection of osteoporosis. Settings and Design: Patients, attendants, volunteers visiting the Dow Radiology and Patel Hospital participated in this cross-sectional study. Materials and Methods: Female participants aged 25-85 years were selected randomly. DXA scan was performed to determine bone mineral density. OPG was performed to measure HS. Correlation between the two was studied in a sample of size of 174 females. Statistical Analysis: Statistical analysis was done by using the Statistical Package for the Social Sciences version 16. For intragroup comparisons, Kruskal-Wallis Test was applied in the groups where normality assumption was not fulfilled. One-way analysis of variance was applied to evaluate the significance between subgroups. For multiple comparisons in the subgroups of both groups, Tukey′s B test was applied. Independent samples t-test was applied for intergroup comparison. Results: Highly significant decrease in height HS was observed in intergroup comparison of Group I (P < 0.001) and Group II (P < 0.001). In intergroup comparisons between subgroups of Groups I and II, significant decrease in HS was observed between osteopenic and osteoporotic subgroups (P = 0.038 and P = 0.001, respectively), and highly significant decrease between normal participants (P < 0.001). Conclusion: Because the decrease in HS is seen in younger and older groups of females at osteopenia stage, this variable can be conveniently used for early detection of osteoporosis for both age groups. The findings conclude that the OPG can be used as a screening tool for osteoporosis.